Litter Fall and Nutrient Return in Quercus Cerris L. Var. Cerris Forests in the Central Black Sea Region of Turkey - Kutbay, Hamdi Güray; Horuz, A. (Pakistan Botanical Society, 2001)
Litter fall and nutrient return in a deciduous Quercus cerris L. var. cerris forest which constitutes the "étage supra-mediterranéen pré-pontique" vegetation layer in the Central Black Sea Region of Turkey were investigated. Total annual input of litter was 681.90 g m-2 of which 64% was leaf litter fall, followed by 27, 7 and 2% wood, reproductive and miscellaneous litter fall, respectively. The annual nutrient return through litter fall was 42.70 kg ha-1 N, 2.62 kg ha-1 P, 44.37 kg ha-1 K, 85.78 kg ha-1 Ca and 15.54 kg ha-1 Mg. High turnover rate was found in the present study. However, turnover time was lower than other Quercus forests.